Faktor-Faktor yang Berhubungan dengan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Kuanfatu Kabupaten Timor Tengah Selatan - Edmon Juldaimon Kase; Sintah L. Purimahua; Mustakim Sahdan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Stunting is a manifestation of growth failure (growth faltering), namely when a child's height is shorter than the normal height of children his age. The main factor causing stunting is poor nutritional intake from the initial period of fetal growth until the child is two years old. This study aims to analyze factors related to the incidence of stunting among toddlers in the Kuanfatu Community Health Center working area, South Central Timor Regency. This type of research is an analytical survey with a cross sectional study design. The population in this study were all toddlers in the Kuanfatu Community Health Center working area with a total of 1706 toddlers with sampling using a simple random sampling technique. The results of this study show that there is a relationship between economic status (p=0.006), history of LBW (p=0.000), birth interval (p=0.001), and sanitation and hygiene (p=0.005) with the incidence of stunting among toddlers in the Kuanfatu Community Health Center working area. South Central Timor Regency. It is hoped that families and community health centers will play an active role in providing education and intervention to toddlers in efforts to combat stunting.